2019
DOI: 10.1002/ldr.3492
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining crop production in China's cropland by crop residue retention: A meta‐analysis

Abstract: Crop residue retention (RR) is a recommended practice in China and globally. However, comprehensive assessment of changes and mechanisms affecting crop production and soil processes with RR and thus identifying systems of sustainable residues management are not widely studied. A national meta‐analysis was conducted to assess changes in 24 indicators (related to soil quality, soil nutrients, crop yield, and environmental impacts) along with their relationships under RR through 4,910 comparisons from 278 publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(58 citation statements)
references
References 86 publications
4
52
1
1
Order By: Relevance
“…This can solve problems that can't be solved by a single study. The effects of crop residue return on crop yields and WUE have been widely investigated using different methods, including meta-analysis [19,20,21]. For example, by applying a meta-analysis method, Yu et al [20] showed that crop residue return can significantly improve maize grain yields and WUE in Northern China because it enhances the soil hydrothermal environment.…”
Section: Introductionmentioning
confidence: 99%
“…This can solve problems that can't be solved by a single study. The effects of crop residue return on crop yields and WUE have been widely investigated using different methods, including meta-analysis [19,20,21]. For example, by applying a meta-analysis method, Yu et al [20] showed that crop residue return can significantly improve maize grain yields and WUE in Northern China because it enhances the soil hydrothermal environment.…”
Section: Introductionmentioning
confidence: 99%
“…SOC accumulation and sequestration in agro-ecosystems rely on the C input from crop straw (shoot, root, and root exudates) and C output from SOC mineralization by soil microbes [4]. In the past, crop straw was widely used for soil amendment, cooking and heating, animal feed, and biofuels; among all these uses, straw returning is considered to be one of the best practices environmentally [5]. Crop straw not only provides a source of fresh organic matter, but also increases crop yield [6].…”
Section: Introductionmentioning
confidence: 99%
“…Residue retention is an effective management technique to enhance SOM content and improve soil nutrient availability [12,54,55] However, the climate in Northeast China is characterized by an extremely long and cold winter [33]. Therefore, the residue buried in soil after harvest in mid October had difficulty decomposing during the winter, owing to the deficiency of water and heat [8].…”
Section: Effects Of Residue Management On Soil Bacterial and Fungal Cmentioning
confidence: 99%
“…Residue retention is an effective strategy for recycling crop residues and a beneficial practice to improve soil fertility and crop productivity [10]. Numerous studies have proven that residue retention not only increases the soil carbon stock [11] but also improves the water-holding capacity of the soil [12]. However, adverse effects of no tillage practices or residue retention have sometimes been reported depending on cropping practices, land use types and adoption years [12,13] As critical soil components, microorganisms play key roles in soil nutrient biogeochemical cycling, substantially contributing to soil structure and maintaining ecosystem functions [14,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation